2011
DOI: 10.1007/s11259-011-9463-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific plasma biochemistry reference ranges in <1 year old dogs in Japan

Abstract: The purpose of this study was to investigate and propose possible reference intervals of plasma biochemical analytes in young dogs (<12 months old) in Japan, using 896 canine plasma samples, collected from an array of veterinary clinics throughout the greater Tokyo metropolis area in Japan. The following biochemical parameters were assessed: albumin (ALB), alanine aminotransferase (ALT), alkaline phosphatase (ALP), amylase, aspartate aminotransferase (AST), blood urea nitrogen (BUN), creatinine (CRE), glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…Albumin and creatinine concentrations dropped below the lower RL in dogs older than 14 years, whereas the highest levels were observed in adult dogs. Our results are relatively consistent with previous research showing lower albumin [23,70,71] and creatinine [14,22,24,70,71] levels in puppies and young dogs than in adult dogs, and decreasing albumin [2426] and creatinine [14,24] levels in old dogs. Creatinine concentration is affected by lean body mass [72,73] whereas low albumin level is predictive of poor muscle mass and may increase the risk of sarcopenia in the elderly [74].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Albumin and creatinine concentrations dropped below the lower RL in dogs older than 14 years, whereas the highest levels were observed in adult dogs. Our results are relatively consistent with previous research showing lower albumin [23,70,71] and creatinine [14,22,24,70,71] levels in puppies and young dogs than in adult dogs, and decreasing albumin [2426] and creatinine [14,24] levels in old dogs. Creatinine concentration is affected by lean body mass [72,73] whereas low albumin level is predictive of poor muscle mass and may increase the risk of sarcopenia in the elderly [74].…”
Section: Discussionsupporting
confidence: 93%
“…Due to artificial selection, there are more than 400 genetically, morphologically, physiologically and behaviourally different dog breeds that represent closed genetic populations with high intra-breed homogeneity and high interbreed heterogeneity [6][7][8][9], suggesting that breeds would differ also metabolically [10][11][12]. Previous studies have identified variation in haematological and clinical chemistry analytes due to breed [13][14][15][16][17][18][19][20] and age [14,[21][22][23][24][25][26], for example. In humans, sex differences in metabolism have been demonstrated [5,27,28], suggesting that similar effects could be evident also in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the reference intervals (RIs) comprise values referred to the 95% of a healthy population, they have become one the most commonly used tools in clinical decisions [ 2 ]. However, only a few laboratories perform their reference studies, and most RIs consider values obtained from adult dogs; hence, those references should not be used to interpret test results in puppies [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…BV estimates in people are made in clinically healthy individuals, even though resulting data are intended to be applied to all populations (sick, adult, geriatric, and so on) . Although mean values for laboratory results can vary by sex, health status, breed, and age, the inherent biological variability around a given homeostatic set point appears constant, even in chronic disease states . This suggests that BV data from our study are likely applicable to most horses, not just healthy, nonathletic mares.…”
Section: Discussionmentioning
confidence: 98%